Nomos and the Dispute in Galatians 2: A Case of Conflicting By-Laws - Lavender, Jordan (Religions, 2023)
This research explores the interpretation of nomos in Galatians 2:11–21 within the light of Greco-Roman associations and Palestinian chavurot. As such, it proposes a reading of the text and conflict as a localized issue of conflicting association by-laws between Jews and Gentiles. The members of Jacob’s association in Jerusalem demonstrated Pharisaic behavior in requiring circumcision for membership in the association and requiring the additional observance of purity and tithing regulations as interpreted by the association as crucial elements of its by-laws. Paul chastises Peter for breaking the by-laws of the Jewish assembly when eating with the Gentiles but then “separating himself” from them and requiring the Gentiles to observe the by-laws that he had just broken. Paul then explains how the Jewish association’s by-laws are not required for his Gentile followers and redirects them to the faithfulness of Christ as their means of being set right and the means of acquiring justice.